(untitled) (Journal of the College of Basic Education, 2022)
The Arabic language is distinguished by its attention to the meaning that its structures perform, as each word has a place in the structure that is required by the meaning, required by the formulation, and called for by the context (), as well as taking into account the technical aspect that the language structures perform. The situation to be communicated becomes evident, and it has a good impact on the recipient, and thus the judgment is made on the eloquence of speech, and its eloquence stems from the link between grammar and the characteristics of the composition, which is the main concern of the scholars of Arabic rhetoric ().It does not necessarily require structural transformations; In order to reach the stylistic structure, simply linking the form to the content, or linking a group of words to each other, but the transformation goes beyond the joining process to the commenting process, as grammatical relations play an informative, adult role.